Strategi Pertahanan Keamanan Siber Berbiaya Rendah untuk UMKM: Tinjauan Literatur - Pratama, Nugraha Adhi; Nugraha, Muhammad Rizki (GLOBAL SCIENTS PUBLISHER, 2026)
Digital transformation is driving Micro, Small, and Medium Enterprises (MSMEs) to adopt information technology in their business activities. However, reliance on digital systems increases cybersecurity risks, while limited resources are a major obstacle for MSMEs in implementing comprehensive security systems. This study reviewed 18 scientific articles related to low-cost cybersecurity defense strategies applicable to MSMEs. The review results indicate that MSMEs are vulnerable to cyber threats due to budget constraints, low security literacy, and weak information governance. A realistic strategy emphasizes three key aspects: people, processes, and simple technology, through education and training, basic security policies, consistent operational procedures, and the use of affordable technology. This study is expected to serve as a reference for MSMEs and researchers in designing effective, efficient, and sustainable cybersecurity strategies.